2002
DOI: 10.1007/bf02897977
|View full text |Cite
|
Sign up to set email alerts
|

Relation between self-reported weight cycling history, dieting and bio-behavioral health in Japanese adult males

Abstract: Background: Epidemiological findings suggest that weight fluctuations are associated with unfavorable health outcomes compared with stable weight. However, the interrelationship between the weight cycling history and dieting status in a non-clinical male trial on the risk for bio-behavioral health is unclear.Objective: The purpose of this study was to examine the relation between weight cycling history as a result of intentional weight loss and bio-behavioral health in Japanese adult males.Method: A cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Other studies conducted in university students exercise stages of change are more clearly identified the higher exercise stages of change level in men than their women counterparts (Wallace et al, 2000;Wakui et al, 2002;). A related finding was found in the study of Suminski and Petosa (2002).…”
Section: Stages Of Change Model and Physical Activitymentioning
confidence: 90%
See 1 more Smart Citation
“…Other studies conducted in university students exercise stages of change are more clearly identified the higher exercise stages of change level in men than their women counterparts (Wallace et al, 2000;Wakui et al, 2002;). A related finding was found in the study of Suminski and Petosa (2002).…”
Section: Stages Of Change Model and Physical Activitymentioning
confidence: 90%
“…Previously, exercise stages of the changes have been studied with different population in many countries around the world, including United States, Canada, Australia, United Kingdom, 15 European Union countries, the Netherlands, China, Malaysia, Japan, and Mexico. (Juniper et al, 2004;Nigg and Corneya, 1998;Prapavessis et al, 2004;Wakui et al, 2002). A meta-analysis by Spencer et al (2006) (Ronda et al, 2001).…”
Section: Stages Of Change Model and Physical Activitymentioning
confidence: 99%
“…Although there is controversy in the literature about whether or not yo-yo dieting can lead to problems involving gall bladder and liver, 15, 38 data are overall supportive that weight loss decreases risk factors associated with major diseases such as cancer. 39 With respect to cardiovascular diseases, there is still controversy based on the idea that weight cycling, particularly in younger individuals, may result in fluctuations of heart rate, blood pressure, sympathetic activity, glomerular filtration rates and circulating glucose and lipid levels that may alter heart development and/or cause lipotoxic events influencing cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…7, 8, 9, 10, 11, 12, 13, 14, 15, 16 Some studies find increased health risks associated with weight cycling, while others do not. A major drawback of these studies is the lack of consistency in the definition of weight cycling.…”
Section: Introductionmentioning
confidence: 99%